ON A NEW SPECIES OF THE GENUS Dorylaimus (NEMATODA: DORYLAIMIDAE) FROM JALNA DISTRICT (MS) INDIA - BAROTE, VISHNU K.; BAROTE, RAOSAHEB K.; BORDE, SUNITA N. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
A Specimen of the genus Dorylaimus was found in soil around the root of the soybean crop in Jalna district (M.S) India. The species is characterized by the body being circular. The body is ventrally curved upon fixation tapering toward both sides, cuticle thick at mid-body. Lip is separated angular, lateral chord about 1/4th to 1/3rd of the body. Guiding is ring single, pharynx odontostylet, length is long. The female genital system is amphidelphic, both the sexual branches are equally developed. Oviduct was joined ovary sub terminally, sphincter present in oviduct uterus junction. The tail is straight and long.